Development of the occupational safety in the food industry with regard for the risk-based approach - Evtushenko, Olga; Siryk, Alina; Porodko, Petro (My University, 2016)
The prediction of occupational risks and making the conditions for the prevention of injuries based on it is one of the promising scientific directions of the workplace safety development in industry, as it is directly connected with the manufacturing process.
Keywords: safety; labor; traumatism; risk; безпека; праця; травматизм; ризик; безопасность; труд; риск; кафедра екології та екоменеджменту